Catalina María Doria y las instituciones carmelitanas en la Lima del siglo XVII - Rouillon Almeida, Denisse (2011)
The creation in Lima of the first Carmelite religious training center took place in the first half of the 17th century. Said establishment refers preliminarily to the reform of Saint Teresa, begun in the previous century and recognized for its decisive influence on the female and male branches of the Carmelite order. In this environment of ecclesiastical renewal, the Lima foundation of the first Carmelite institution took place, under the modality of “recollection”. This research considers relevant the identification of those who participated in the creation of that religious training center in Peru, which is why the fundamental leadership of Catalina María Doria stands out, as an institutional figure and important follower of Saint Teresa of Ávila. The article refers to the importance of the school as a center for colonial female education and the origin of the first monastery of the aforementioned order in the Peruvian viceroyalty.